2008
DOI: 10.1080/17450390801892633
|View full text |Cite
|
Sign up to set email alerts
|

Responses of whole body protein synthesis and degradation to plantain herb in sheep exposed to heat

Abstract: An experiment including a [1-(13)C]leucine isotope dilution and a nitrogen balance were carried out to determine the effect of feeding plantain herb (Plantago lanceolata L.) on whole body protein synthesis (WBPS) and degradation in sheep kept at thermoneutral temperature (20 degrees C) or exposed to heat (30 degrees C). The animals were fed either mixed hay of orchardgrass and reed canarygrass (Hay-diet) or Hay-diet and plantain (9:1) (PL-diet) at maintenance level using a crossover design. Nitrogen intake was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 34 publications
4
9
3
Order By: Relevance
“…Al-Mamun et al . [43] reported that plasma LeuTR decreased but the WBPS remained unchanged in sheep fed on plantain herb compared with fed on mixed hay, which partly agrees with our present findings. Li et al [44] used [ 15  N]glycine as the tracer to determine the effect of a Chinese herbal medicine mixture (Astragalus root and Angelica root, same as the present study) on protein metabolism in nephrotic patients, and observed that Chinese herbal medicine could improve the disorder of protein metabolism and increase the level of serum protein by improving the net rate of protein synthesis.…”
Section: Discussionsupporting
confidence: 93%
“…Al-Mamun et al . [43] reported that plasma LeuTR decreased but the WBPS remained unchanged in sheep fed on plantain herb compared with fed on mixed hay, which partly agrees with our present findings. Li et al [44] used [ 15  N]glycine as the tracer to determine the effect of a Chinese herbal medicine mixture (Astragalus root and Angelica root, same as the present study) on protein metabolism in nephrotic patients, and observed that Chinese herbal medicine could improve the disorder of protein metabolism and increase the level of serum protein by improving the net rate of protein synthesis.…”
Section: Discussionsupporting
confidence: 93%
“…Al-Mamun et al (2008) observed that, plantain increased body protein synthesis in sheep exposed to heat; our experiment was performed in temperature around 30 0 c and found the increased body weight of broiler than control group which is similar with Al-Mamun et al (2008). It was also reported that, poor lamb growth on the PL cultivar 'Grasslands Lancelot' (Fraser & Rowarth, 1996) which is contradictory with this result.…”
Section: Discussioncontrasting
confidence: 52%
“…Plantain is important from the animal feeding point of view because of its medicinal value to animals, improving their physiological conditions and diminishing the need for antibiotic growth promoters. Moreover, Plantain is not only a source of bioactive components but also a good source of protein and minerals (Al-Mamun et al 2008). Plantain was reported to contain tannins, thus they, too, might affect carcass composition (Dorfler and Roselt 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Al‐Mamun et al. () deduced that it takes a relatively long period for sheep to get adjusted to new stable conditions in digestive function. Sano, Nakamura, Kobayashi, Takahashi, and Terashima () also observed an unchanged CP digestibility in sheep exposed to cold for 18 days.…”
Section: Discussionmentioning
confidence: 99%